Progress in Clinical Neurosciences: Sepsis-Associated Encephalopathy: Evolving Concepts - John X. Wilson; G. Bryan Young (2003)
Systemic sepsis commonly produces brain dysfunction, sepsis-associated encephalopathy, which can vary from a transient, reversible encephalopathy to irreversible brain damage. The encephalopathy in the acute phase clinically resembles many metabolic encephalopathies: a diffuse disturbance in cerebral function with sparing of the brain stem. The severity of the encephalopathy, as reflected in progressive EEG abnormalities, often precedes then parallels dysfunction in other organs. Recent research has revealed a number of potentially important, non-mutually exclusive, mechanisms that have therapeutic implications.